Kolejność, liczba i kształt "biada" w Q: próba rekonstrukcji na bazie Mt 23 i Łk 11 - Rakocy, Waldemar (The Biblical Annals, 2017)
The author seeks to determine the sequence, number and shape of particular “woes” in the source Q. The reconstruction of the sequence of the number of “woes” in Q allows us to a greater or lesser extent come closer to tradition at the basis of Mt and Lk. To determine the shape (even approximate) of individual “woes” remains highly hypothetical (that is why Mt and Lk could use various version of a common tradition). The editorial trends of Mt and Lk suggest only greater or lesser relationship with Q.